Effectiveness of Implementing the Scholarship Program for North Morowali Regency Students - Fadli Abd. Pattah, Moh.; Susanti, Ani; Nuraisyah, Nuraisyah; Haryono, Dandan (Lafadz Jaya Publisher, 2024)
This research is to determine the effectiveness of the scholarship program for North Morowali Regency students. This analysis uses qualitative research with a descriptive approach. The informants for this research were the Head of the Department and Secretary of the Regional Education and Culture Service of North Morowali Regency, as well as three students who received regional scholarships. Information collection uses information techniques, interviews and documentation. In this research, data analysis uses the data condensation framework, data presentation, and drawing conclusions by Miles and Huberman. Meanwhile, the effectiveness indicators used in this research are Program Success, Target Success, Program Satisfaction, and Input and Output Levels. The conclusion of this research is that of the four indicators, target success has not gone well. The aspect of access to information by students is limited. Meanwhile, the other three indicators based on research have been running effectively.